2015
DOI: 10.3168/jds.2014-8388
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Development of the first follicular wave dominant follicle on the ovary ipsilateral to the corpus luteum is associated with decreased conception rate in dairy cattle

Abstract: In this study, we examined the effect of the locations of the first-wave dominant follicle (DF) and corpus luteum (CL) on fertility. In total, 350 artificial insemination (AI) procedures were conducted (lactating dairy cows: n=238, dairy heifers: n=112). Ovulation was confirmed 24 h after AI. The locations of the first-wave DF and CL were examined 5 to 9d after AI using rectal palpation or transrectal ultrasonography. Lactating dairy cows and dairy heifers were divided into 2 groups: (1) the ipsilateral group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 13 publications
(16 reference statements)
2
14
0
Order By: Relevance
“…4 hCG treatment = Cows were treated with hCG (1500 IU) at five days from ovulation. 5 Day 5 = Ovulation day was defined as Day 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 hCG treatment = Cows were treated with hCG (1500 IU) at five days from ovulation. 5 Day 5 = Ovulation day was defined as Day 1.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have reported that the development of the first-wave DF ipsilateral to the corpus luteum (CL) was associated with reduced conception rates in lactating dairy cows [5] and the conception rate could be improved by administrating human chorionic gonadotropin (hCG) only to the cows having the first-wave DF ipsilateral to the CL at 5 days after artificial insemination (AI) [6]. However, we could not clarify the mechanism underlying the low fertility when the first-wave DF was ipsilateral to the CL and the physiological mechanisms of increasing conception rate by hCG treatment with the first-wave DF ipsilateral to the CL at 5 days after AI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the location frequency of contralateral relationship between the PF and CL is greater in heifers with the three follicular waves (Ginther et al 2014). In dairy heifers, the first-wave dominant follicle (DF) located ipsilateral to the CL in the ovary is associated with reduced conception rates (Miura et al 2015). Thus, it was possible that when the PF developed in the left ovary there was a high probability that the PF had developed from the third follicular wave; therefore, in this study, the conception rate may be higher when the PF developed in the left ovary.…”
Section: Discussionmentioning
confidence: 99%
“…However, the locational relationships among the PF, regressed CL and number of follicular waves were not confirmed in this study. In dairy heifers, the first-wave dominant follicle (DF) located ipsilateral to the CL in the ovary is associated with reduced conception rates (Miura et al 2015). Further research is required to clarify the mechanism underlying higher conception rates when the PF develops in the left ovary to confirm the relationships among the number of follicular waves, locational relationship of regressed CL and PF, and locational relationship of the first-wave DF and CL in dairy heifers.…”
Section: Discussionmentioning
confidence: 99%